E-commerce in Pakistan: Prospects and Challenges - Dost Muhammad Barrech,; Dr. Muneera,; Aftab Aslam,; Rashid Manzoor,; Munir Ahmed, (Al-Qanṭara, 2023)
In the era of globalization and science & technology, E-commerce has gained considerable significance. In the post-Covid-19 period, the importance of E-commerce has further augmented. States leave no stone unturned to capitalize on the potential of E-commerce. Pakistan, currently, is the 37th largest E-commerce market worldwide, with market revenues successively increasing over the past 3 years. The industry has potential as the number of internet users is enhancing by leaps and bounds which will in turn manifest innovation and improve E-commerce business. Pakistan can learn from leading economies by improving its supply chain management system through logistics and distribution networks. Many companies are incorporating their products in the digital sphere, Vans and Coca-Cola. The gaming industry has untapped potential in Pakistan. The latter is producing major corporations such as Walmart and Amazon basics which highlights its capacity. Meanwhile, challenges faced by the E-commerce industry in Pakistan range from, a lack of trust by consumers whether in the product or payment method, to a reliable payment mechanism for instant transactions such as PayPal, and cash on the delivery payment method which slows economic activity. More importantly, the absence of an efficient logistics network hinders economic activity altogether. This paper, thus, will comprehensively analyze the potential of E-commerce and will shed light on the prospects and challenges faced by the emerging economy and will give policy recommendations to modernize the E-commerce market. Key Words: Walmart, Amazon, B2B, Globalization, Internet, Companies, Young Bulge